The Importance of Children’s Ministry at All Saints Church of Uganda Kyotera Kakoma Archdeaconry West Buganda Diocese - James Mubiru (Uganda Christian University, 2024)
This study labored to give the importance of Children's ministry in All Saints Church of Uganda Kyotera and found that; children's ministry helps in the following; knowing the truth about God, the continuity of the Church, Church growth, source of Joy and develop Children among others therefore, pastors should try their best to do this ministry well through training Children's teachers, building Children's Church, having a curriculum, and having a budget to facilitate this ministry. The study has established that the number of children at All Saints Kyotera Church of Uganda and West Buganda Diocese at large is growing but the children’s ministry is not given sufficient support from the clergy because they are attending to the bigger issues of the church. There are still many people in the congregations who treat children as second-class human beings who should not be heard. Children ministries are viewed as welcoming of children, but most respondents understood the significance of children only as recipients of Christian education and care. Clergy cannot provide examples of how their churches are sanctuaries of vulnerable children that need compassion and the majority of the clergy and Christians are unsure of how their church is blessing children. The study focuses on revealing the principal aim of the children’s ministries in the Church is to teach children about Jesus. However, the children’s ministries also emphasized discipline and morals. All the churches that were the focus of this study had children’s workers who were trained and were receiving continuing ministry training. The Church had developed a curriculum for children’s ministry, capacity building was done for children’s ministry workers, and music was incorporated into the children’s ministry curriculum. Media and visual aids were used in teaching children and bible games were incorporated in the children’s ministry curriculum. However, resources for curriculum implementation were inadequate.